2021
DOI: 10.1038/s41467-021-27528-6
|View full text |Cite
|
Sign up to set email alerts
|

NuMA regulates mitotic spindle assembly, structural dynamics and function via phase separation

Abstract: A functional mitotic spindle is essential for accurate chromosome congression and segregation during cell proliferation; however, the underlying mechanisms of its assembly remain unclear. Here we show that NuMA regulates this assembly process via phase separation regulated by Aurora A. NuMA undergoes liquid-liquid phase separation during mitotic entry and KifC1 facilitates NuMA condensates concentrating on spindle poles. Phase separation of NuMA is mediated by its C-terminus, whereas its dynein-dynactin bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…The spindle is regarded as a condensate with liquid–crystalline properties ( 194 ). The LLPS of key proteins involved in spindle function was demonstrated in recent publications ( 195 , 196 ).…”
Section: Par In Condensates From a Macrostructural Point Of View Trul...mentioning
confidence: 83%
See 2 more Smart Citations
“…The spindle is regarded as a condensate with liquid–crystalline properties ( 194 ). The LLPS of key proteins involved in spindle function was demonstrated in recent publications ( 195 , 196 ).…”
Section: Par In Condensates From a Macrostructural Point Of View Trul...mentioning
confidence: 83%
“…In acentrosomal human cells, overexpressed NuMA was reported to form multiple condensates that promote spindle bipolarization by organizing microtubule asters ( 198 ). Recently, it became known that at spindle poles, endogenous NuMA also forms numerous condensates, which concentrate tubulins, bind microtubules, and enrich crucial regulators ( 195 ). These condensates manifest liquid-like behavior by fusion and fissure, are sensitive to 1,6-hexanediol, and exhibit rapid FRAP recoveries.…”
Section: Par In Condensates From a Macrostructural Point Of View Trul...mentioning
confidence: 99%
See 1 more Smart Citation
“…In mitotic cells, NUMA at the spindle poles forms insoluble aggregates upon microtubule depolymerization (68)(69)(70)(71)(72). To test whether NUMA forms similar cytoplasmic aggregates in aMTOC-free mouse oocytes, we depolymerized spindle microtubules acutely with nocodazole and prolonged cold treatment.…”
Section: Numa Organizes the Spindle Poles In Human Oocytesmentioning
confidence: 99%
“…The mitotic spindle composed of microtubules is crucial for the assembly and separation of chromosomes during cell division of the eukaryotic cells, and the formation of the mitotic spindle is related to phase separation. It was shown that the NuMA protein regulates the organization, structural dynamics, and functions of the mitosis spindle through liquid-liquid phase separation (LLPS) controlled by Aurora-A phosphorylation ( 55 ).…”
Section: Recent Trends In Research Of Biomolecular Llpsmentioning
confidence: 99%